Being attractive brings advantages: the case of parrot species in captivity - Frynta, Daniel; Lisková, Silvie; Bültmann, Sebastian; Burda, Hynek (PLoS One, 2010)
BACKGROUND: Parrots are one of the most frequently kept and bred bird orders in captivity. This increases poaching and thus the potential importance of captive populations for rescue programmes managed by zoos and related institutions. Both captive breeding and poaching are selective and may be influenced by the attractiveness of particular species to humans. In this paper, we tested the hypothesis that the size of zoo populations is not only determined by conservation needs, but also by the perceived beauty of individual parrot species assessed by human observers. METHODOLOGY/PRINCIPAL FINDINGS: For the purpose of data collection, we defined four sets of species (40 parrots, 367 parrots, 34 amazons, 17 macaws). Then, we asked 776 human respondents to evaluate parrot pictures of the selected species according to perceived beauty and we analyzed its association with color and morphological characters. Irrespective of the species set, we found a good agreement among the respondents. The preferred species tended to be large, colorful, and long-tailed. CONCLUSIONS/SIGNIFICANCE: We repeatedly confirmed significant, positive association between the perceived beauty and the size of worldwide zoo population. Moreover, the range size and body size appeared to be significant predictors of zoo population size. In contrast, the effects of other explanatory variables, including the IUCN (International Union for Conservation of Nature) listing, appeared insignificant. Our results may suggest that zoos preferentially keep beautiful parrots and pay less attention to conservation needs.
Keywords: Population Dynamics; zvířata v ZOO; Animals, Zoo; populační dynamika; zvířata; Breeding; Animals; lidé; Adult; dospělí; Beauty; papouškovití; Female; Male; ohrožené druhy; ženské pohlaví; mladý dospělý; Humans; mužské pohlaví; Young Adult; chov; krása; Endangered Species; Parrots